My real children - Walton, Jo (Tor, 2014)
It's 2015, and Patricia Cowan is very old. "Confused today," read the notes clipped to the end of her bed. She forgets things she should know-what year it is, major events in the lives of her children. But she remembers things that don't seem possible. She remembers marrying Mark and having four children. And she remembers not marrying Mark and raising three children with Bee instead. She remembers the bomb that killed President Kennedy in 1963, and she remembers Kennedy in 1964, declining to run again after the nuclear exchange that took out Miami and Kiev. Her childhood, her years at Oxford during the Second World War-those were solid things. But after that, did she marry Mark or not? Did her friends all call her Trish, or Pat? Had she been a housewife who escaped a terrible marriage after her children were grown, or a successful travel writer with homes in Britain and Italy? And the moon outside her window: does it host a benign research station, or a command post bristling with nuclear missiles? Two lives, two worlds, two versions of modern history; each with their loves and losses, their sorrows and triumphs. Jo Walton's My Real Children is the tale of both of Patricia Cowan's lives...and of how every life means the entire world.